Reading Comprehension as Critical Practice: Empowering Students through CDA Based Learning - Baihaqi, Baihaqi; Suhadi, Jumino; Pratiwy, Devi (ITScience (Information Technology and Science), 2025)
This study aimed to empower students reading comprehension at MTs MIM Langsa through CDA based learning. Teaching reading should not merely focus on sentence structure and memorizing new vocabulary items. Teachers should encourage students to read through the content. CDA based learning in critical practice to reading comprehension Will empower students skill in reading practice. The method used is quantitative research by applying questionnaire and interview with the respondents. The participants consisted 20 students from eighth-grade students selected as primary source of data from which the researcher observed their difficulties and the factors of causing the students difficulties in reading comprehension. The result find 12 students (60%) face dificulty in reading comprehension, 7 students (35%) obtains difficulty in identifying main idea, 14 students (70%) face difficulty in making inferences, 8 students (40%) face difficulty in identifying supporting details and 9 students faces dificulty in understanding correct vocabulary. It was concluded that CDA based learning empower students comprehension and make the students read based on the discourse aspects: social, discursive and textual, hopefully can help the students as readers enjoying their reading and make reading as a habit.